KEADAAN FASILITAS SANITASI TEMPAT PELELANGAN IKAN 01 SEOATI KABUPATEN SIOOARJO TAHUN 2013 - Luqman Amyrul Hakim; Sri Mardoyo; Margono . (GEMA LINGKUNGAN KESEHATAN, 2014)
The fish auction place is considered as a public place, where people do their transactions onfishery products. Sedati fish auction place is a center of a fishery products in the eastern coast ofKabupaten Sidoarjo. Everyday large number of people aredoing transactionsthat generated large amountof garbage and trash. Therefore sanitation facilities in such a place need to be controlled.This is a descriptive observation, to make a description about condition of the sanitation facilitiesin Sedati fish auction center, using investigation formsreleased by ministry of health number: 519/MENKES / SK / VI /2008.The observation lead to statements that condition of sanitation facilities in the place wasunhealthy (45% ) as follow: the location and buildingsthat were in poor condition was 62%. The cleanwater storage facilities were 50%. Toilet sanitation and hand wash facilities were 32%. The seweragesystem was 12%. The garbage containers were 32%. The desinfection and animal/vector related facilitieswere 32%. The supporting facilities were 56%, all received unhealthy appraisal criteria.The study suggested the management of the Sedati fish auction place to make signsin moreclearly wording to separate wet and dry fish tables. Hand washingfacilities need to be added in the fishselling sites. Storage should be provided to store fish at cold temperature. Strong and watertight garbagecontainers are in need in the area, supply of clean water is also required. Disinfection should be performedonce every month until the condition of the Sedati fish auction place improves, clean and free of germs.The management need to be ready with first aid kits and fire extinguisher.